WHEN THE FOX GUARDS THE HENHOUSE: DARK TRIAD TRAITS AS DRIVERS OF INCIVILITY AND BROKEN KNOWLEDGE PATHS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
Academic institutions have witnessed a sharp increase in asocial behaviors such as incivility and knowledge hoarding across the globe. Such behaviors, a common type of interpersonal misconduct, undermine the collaborative spirit and disturb the harmony between students and instructors. Several variables, including social, cultural, emotional, and institutional drivers, are identified in the research as contributing to academic incivility. Despite the extant literature on the said domain, there hasn’t been much empirical research on the influence of individual personality qualities, especially dark personality traits. Previous research indicates a strong correlation between core personality traits and individual behavior patterns, emotional reactions, and interpersonal conduct. While substantial research has examined the role of dark traits in areas such as leadership behavior, investment decisions, and risk-taking tendencies, there remains a significant gap in understanding how these traits manifest in academic environments. The present study attempts to fill this gap.
Keywords: Incivility, knowledge hoarding, misconduct, dark personality traits, academic, etc.